PERENCANAAN POLDER SEBAGAI ALTERNATIF PENGENDALI BANJIR PADA DAS SEMPAJA KOTA SAMARINDA PROVINSI KALIMANTAN TIMUR - ANSYAH, RIDU (KURVA S JURNAL MAHASISWA, 2013)
ABSTRACK Watershed of Sempaja Samarinda, province of East Kalimantan through many changes in land use, both uptream and downstream of the watershed. This Significant changes has resulted of flooding in Sempaja Watershed.To anticipate flood problems in Sempaja Watershed, polder planed as an alternative flood control. The result planning polder on Watershed of Semapaja Samarinda is based on the design flood discharge over a periode of 25 years and calculated using the pump with 18m3/sc capasity we have dimensions of the polder. The polder have 900m long, 450m wide and 3m deep of dimensions. This polder can accommodate 1.215.000 m3 flood.